Diseño de un modelo de cargue automático de cascara de nuez para el proceso de limpieza del turboexpander de la unidad cracking catalítico en la empresa Ecopetrol (2023)
This research seeks to design a model for automatic walnut shell loading to the turboexpander cleaning process of the cracking plant at Ecopetrol to optimize productivity. In order to improve the working conditions of the operators, improve the cleaning system and therefore reduce the risk of plant failure in the cracking unit, analysis of the existing processes and diagnosis of the current conditions of the loading system were developed. walnut shell, food that nourishes the gas expander turbine, taking into account the requirements in ergonomics and needs of the plant, the characteristics that the model must contemplate and how it is articulated to production were determined.